Pre-Service Early Grade Teachers Attitude Towards Mathematics in Ghana - Amusuglo, Marlene Kafui; Jančařík, Antonín; Marcom, Guilherme Stecca; Kleinke, Maurício Urban (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2024)
This study assessed the reliability of the Attitudes Towards Mathematics Inventory (ATMI) among first-year pre-service early-grade teachers from two Colleges of Education in Ghana. The research involved data collection, instrument adaptation, and statistical analysis. The ATMI, originally consisting of 40 items on a 5-point Likert scale, was used. However, the Likert scale was modified to a 4-point version by eliminating the neutral point. A total of 172 participants took part in the study, and the items demonstrated good internal consistency, with Cronbach’s alpha exceeding 0.70, indicating the reliability of the ATMI for use in the Ghanaian context. The study also employed Exploratory Factor Analysis (EFA) to analyse the ATMI data effectively and identified 28 out of the 40 items. These 28 items were organised into four unique factors: enjoyment, confidence, the usefulness of mathematics, and parent/teacher expectations of mathematics influencing self-efficacy in mathematics among pre-service early-grade teachers.